LINE-1 DNA Methylation, Smoking and Risk of Parkinson’s Disease - Nielsen, Susan Searles (2012)
Long interspersed nucleotide element-1 (LINE-1) retrotransposons are located throughout the human genome. Those retaining an intact 5′ promoter can copy and insert themselves into the DNA of neural progenitor cells that express tyrosine hydroxylase, which may influence differentiation and survival of these cells. Because LINE-1 promoter methylation is associated with decreased LINE-1 propagation, we compared LINE-1 methylation profiles in blood mononuclear cells between 292 newly diagnosed Parkinson’s disease (PD) cases and 401 unrelated, neurologically normal controls. Overall, PD was not associated with percent methylation of the LINE-1 promoter. However, the predictable inverse association between PD and ever smoking tobacco was strongest for men and women with the lowest LINE-1 promoter methylation, and less apparent as LINE-1 methylation increased. Underlying this possible interaction, ever regularly smoking tobacco was associated with decreased LINE-1 methylation in controls (age- and sex-adjusted linear regression β = −0.24, 95% confidence interval [CI] −0.43, −0.04), but not in cases (β = 0.06, 95% CI −0.17, 0.28, interaction p = 0.06). PD cases may have innate differences in their ability to respond to tobacco smoke.